Monetary commitment, institutional constraints and inflation: empirical evidence for OECD countries since the 1970s - Andreas Freytag; Friedrich G. Schneider (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
Central bank independence (CBI) is a very important precondition for price stability. However, the empirical evidence for a correlation between both is relatively weak. In this paper, this weakness is countered with a) an extended measure of monetary commitment, which includes well-known criteria for CBI and external criteria such as convertibility and exchange rate regimes and b) the argument that monetary commitment can grant price stability best if it is backed by an adequate assignment of economic policy. An empirical assessment with data from four decades confirms the crucial role of monetary commitment for price stability.
Keywords: E50; 330; central bank independence; price stability; monetary commitment; Preisniveaustabilität; Geldpolitik; Regelgebundene Politik; Zentralbankautonomie; Inflation; Schätzung; OECD-Staaten